T-lymphocyte perturbation following large-scale apheresis and hematopoietic stem cell transplantation in HIV-infected individuals - Savkovic, Borislav; Macpherson, Janet L.; Zaunders, John; Kelleher, Anthony D.; Knop, Alison E.; Pond, Susan; Evans, Louise; Symonds, Geoff; Murray, John M. (Clinical immunology (Orlando, Fla.), 2012)
Analysis and mathematical modeling of T-lymphocyte perturbation following administration of granulocyte colony stimulating factor (G-CSF) and two large-scale aphereses are reported. 74 HIV-1 positive antiretroviral-treated individuals were infused with gene- or sham-transduced CD34+ hematopoietic stem cells (HSC) in a Phase II clinical trial. T cell numbers were examined in four phases: 1) during steady state; 2) increases in peripheral blood (PB) following G-CSF administration; 3) depletion post-aphereses and 4) reconstitution post HSC infusion. The present analysis provides the first direct estimate of CD4+ T cell distribution and trafficking in HIV-infected individuals on stable HAART, indicating that CD4+ T lymphocytes in PB represent 5.5% of the pool of CD4+ T lymphocytes that traffic to PB. ► We estimate T lymphocyte distribution and trafficking in HIV-infected subjects. ► We perform mathematical modeling on in-vivo T lymphocyte data. ► Our data is from a recent Phase II clinical trial of an anti-HIV gene therapy. ► We find that CD4+ T cells in peripheral blood represent 5.5% of total CD4+ T cells. ► We provide the first direct in-vivo estimate of T cell distribution during HIV.